Modelación del factor hidráulico de sección para diseñar canales regulares - Calero Proaño, Laura de Jesús (2018)
The channels represent fundamental hydraulic systems that impact on the technical and economic feasibility of the project. The hydraulic design involves two variables, but, an equation is available too. The current bibliography solves the problem by means of tables, graphs, explicit equations of relative application and iterative processes. These solutions are limited to certain channels, computational and approximation packages. The research addresses the problem, developing explicit, operational and flexible models that estimate a hydraulic factor of the section to design the structure. The work was developed in the Hydraulic Laboratory of the Faculty of Engineering, Industry and Construction of the Universidad Laica VICENTE ROCAFUERTE de Guayaquil, managing and validating more than 500 analytical and experimental records. The models were estimated by normalizing the Manning flow resistance equation to find the transformed section function, which was correlated with dimensionless geometric parameters and to calculate the hydraulic factor of section K. This K factor was related to the design parameters of the project to determine the tie, width or slope and design the channel. The Y- tie model calculated with the K-factor models, were evaluated with the determined Y- tie model of Manning and with the Y-tie modelestimated by experimentation, obtaining confidence levels exceeding 98% that validate the developed models. The models of the K factor and the Y- tie model are explicit, operative and reliability, being developed and validated analytical and experimental that contributes scientifically to the hydraulic sciences and optimizes technically and economically the channel designs.